Identification of mutations in the ribosomal protein L5 (RPL5) and ribosomal protein L11 (RPL11) genes in Czech patients with Diamond-Blackfan anemia - Cmejla, Radek; Cmejlova, Jana; Handrkova, Helena; Petrak, Jiri; Petrtylova, Kvetoslava; Mihal, Vladimir; Stary, Jan; Cerna, Zdena; Jabali, Yahia; Pospisilova, Dagmar (Human mutation, 2009)
Diamond-Blackfan anemia (DBA) is a congenital red blood cell aplasia that is usually diagnosed during early infancy. Apart from defects in red blood cell maturation, the disorder is also associated with various physical anomalies in 40% of patients. Mutations in the ribosomal protein (RP) S19 are found in 25% of patients, while mutations in other proteins of the small ribosomal subunit--RPS17 and RPS24--have been found in a fraction of patients. Recently, mutations in RPL5, RPL11, and RPL35a of the large ribosomal subunit have also been reported in several DBA patients. Here, we present the identification of mutations in the RPL5 and RPL11 genes in patients from the Czech DBA Registry. Mutations in RPL5 were identified in eight patients from 6 out of 28 families (21.4%), and mutations in RPL11 in two patients from 2 out of 28 families (7.1%). Interestingly, all 10 patients with either an RPL5 or RPL11 mutation exhibited one or more physical anomalies; specifically, thumb anomalies (flat thenar) were always present, while no such anomaly was observed in seven patients with an RPS19 mutation. Moreover, 9 out of 10 patients with either an RPL5 or RPL11 mutation were born small for gestational age (SGA) compared to 3 out of 7 patients from the RPS19-mutated group. These observations may suggest that mutations, at least in RPL5, seem to generally have more profound impact on fetal development than mutations in RPS19. Since RPL5 and RPL11, together with RPL23, are also involved in the MDM2-mediated p53 pathway regulation, we also screened the RPL23 gene for mutations; however, no mutations were identified.
Keywords: DNA Mutational Analysis; Family Health; lidé; Adult; Diamondova-Blackfanova anemie; Base Sequence; Ribosomal Proteins; registrace; ribozomální proteiny; Female; Infant; dítě; Mutation; Gene Frequency; Humans; zdraví rodiny; mutace; frekvence genu; Česká republika; Registries; mužské pohlaví; mladý dospělý; Czech Republic; ženské pohlaví; Young Adult; Male; Aged; Child; dospělí; Anemia, Diamond-Blackfan; mutační analýza DNA; sekvence nukleotidů; kojenec; senioři